The Relationship Between Diabetes and Hypertension and Mortality in Chronic Kidney Disease Patients in Indonesia - Yonata, Ade; Islamy, Nurul (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Chronic kidney disease (CKD) is a major global health problem that significantly increases morbidity and mortality, mainly due to cardiovascular disease (CVD). In Indonesia, cardiovascular complications account for approximately 42% of deaths among CKD patients. This study aimed to analyze the relationship between diabetes and hypertension with mortality in CKD patients in Indonesia. Objective: To investigate the association between diabetes and hypertension and mortality among chronic kidney disease patients undergoing hemodialysis in Indonesia. Methods: A cross-sectional study was conducted at Dr. H. Abdul Moeloek Regional Hospital, Lampung, from March to May 2024. The study population consisted of end-stage CKD patients undergoing hemodialysis. Data were obtained from medical records and analyzed using the Chi-Square test, with a significance level set at p < 0.05. Results: Of 110 patients, 58% of those with diabetes and 55.1% of those with hypertension died. Both comorbidities showed a significant association with mortality in CKD patients (p = 0.0031 for diabetes, p = 0.019 for hypertension). Conclusion: Diabetes and hypertension significantly increase mortality risk among CKD patients. These findings underscore the importance of comprehensive management of comorbidities to improve survival outcomes in CKD populations